HbA1c increase is associated with higher coronary and peripheral atherosclerotic burden in non diabetic patients. (December 2016) - Scicali, Roberto; Giral, Philippe; Gallo, Antonio; Di Pino, Antonino; Rabuazzo, Agata Maria; Purrello, Francesco; Cluzel, Philippe; Redheuil, Alban; Bruckert, Eric; Rosenbaum, David
Abstract: Background and aims: Prediabetes is associated with an increased risk of developing diabetes and cardiovascular disease. Our objective was to examine the cardiovascular (CV) risk profile of non-diabetic patients with and without prediabetes according to HbA1c, using macroangiopathic imaging biomarkers. Methods: Our population consisted of 272 non diabetic patients aged between 40 and 70 years, with a normal fasting plasma glucose (FPG <5.6 mmol/L) and at least 1 CV risk factor. Exclusion criteria were prior history of CV disease or clinical evidence of advanced renal disease. Prediabetes was defined as an HbA1c value of 5.7–6.4%. Coronary artery calcium (CAC) score as well as mean common carotid intima media thickness (IMT) and plaque presence were assessed using consensus criteria. Results: CAC score was higher in the prediabetes group compared to non-prediabetic subjects (131.7 ± 295.6 vs. 62.4 ± 178.8 AU, p  < 0.001). Prediabetic subjects had higher mean IMT than non-exposed subjects (0.77 ± 0.14 vs. 0.61 ± 0.15 mm, p  < 0.001). The proportion of prediabetic patients with CAC = 0 was significantly lower compared to non-exposed subjects (35% vs. 63%, p  < 0.01). In contrast, the proportion of patients with a CAC >400 was significantly higher in the prediabetes group (10% vs. 3%, p  < 0.05). Moreover, carotid plaques were significantly more present in patients with prediabetes than in the normoglycemic subjects ( p  < 0.01). In a multiple linear regression, IMT was associated with HbA1c continuous levels ( p  < 0.001). In addition, logistic regression showed that higher HbA1c levels were associated with CAC and carotid plaques presence ( p for trend for all < 0.001). Conclusions: Among patients with normal fasting glucose, HbA1c increase is associated with higher coronary and peripheral atherosclerotic burden in non-diabetic patients. Highlights: We studied coronary artery calcium score in subjects with pre-diabetes. We focused on pre-diabetes identified only by HbA1c. HbA1c -identified pre-diabetic patients have high coronary artery calcium score. Coronary artery calcium score was significantly associated with higher HbA1c levels. HbA1c is useful to identify prediabetic individuals with a higher cardiovascular risk profile.